Tuberculous cardiac tamponade presenting as severe hypoxic hepatitis - Valdes Roberto Bollela; Fernanda Guioti Puga; Rodrigo Carvalho Santana (Journal of Health and Social Sciences)
A 57-year-old man was referred to the Emergency Department with epigastric and respiratory dependent pain for six days. The physical examination showed mild jaundice, painful liver and muffled heart sounds. Laboratory tests revealed alanine aminotransferase 14,620 IU/L, bilirubin 10.8 mg/dL and serum lactate 13.9 mmol/L. The chest radiograph revealed diffuse interstitial infiltrate predominantly in the right perihilar region with an increased cardiothoracic index. An abdominal ultrasonography confirmed the hepatomegaly and enlargement of inferior vena cava, while the echocardiogram showed a large pericardial effusion with signs of cardiac tamponade. The patient was transferred to the intensive care unit (ICU) where he underwent a pericardiocentesis. A total of 640 ml of hemorrhagic fluid was drained, with significant clinical improvement after the procedure. Mycobacterium tuberculosis was isolated from the gastric lavage and pericardial fluid cultures. Ten days after admission and cardiac tamponade drainage the patient was recovered, the liver aminotransferases were close to the normal values and the patient presented a progressive clinical and laboratory improvement with the tuberculosis treatment. Tuberculosis cardiac tamponade usually does not have an acute clinical presentation and is a rare but life-threatening cause of severe hypoxic hepatitis, which may lead to mal-perfusion secondary to blood stasis in the liver. As soon as the cause of liver hypoxemia is removed there will be a rapid and impressive improvement in the liver damage and function markers.